Honey Enhances Antibiotic Effectiveness Against Urinary Tract Infections: Madu Meningkatkan Efektivitas Antibiotik Terhadap Infeksi Saluran Kemih - Fejer, Lamyaa Gh.; Hameed, Ghaidaa S.; Ali, Mayssam Hussein Mohammed; Al-Hammood, Orooba (Academia Open, 2024)
Background: Urinary tract infections (UTIs) are prevalent across all ages and genders and pose significant treatment challenges, often requiring alternative therapeutic approaches due to increasing antibiotic resistance. Specific Background: The study examines the impact of antibiotics and honey on bacterial UTIs, revealing 17 cases, primarily caused by Staphylococcus aureus and Klebsiella pneumoniae. Knowledge Gap: The study evaluates the effectiveness of honey in combining antibiotics with anise and spring flower honey, focusing on its potential to enhance antimicrobial effects in UTIs. Results: Biochemical analysis and VITEK diagnostics revealed significant bacterial growth. Antibiotic susceptibility tests showed varied effectiveness, with spring flower honey enhancing the activity of nitrofurantoin (35%), trimethoprim (17.6%), trimethoprim-sulfamethoxazole (23.5%), tetracycline, and norfloxacin (35.2%). Anise honey also demonstrated notable synergistic effects, particularly with norfloxacin (47%) and tetracycline (41%). Novelty: This study highlights the potential of combining honey with antibiotics to combat UTIs, offering new insights into alternative treatment strategies and demonstrating significant synergy with specific antibiotics. Implications: The findings suggest that incorporating honey into UTI treatments could improve therapeutic outcomes and help mitigate the growing issue of antibiotic resistance. Further research is needed to identify active compounds in honey and optimize their use with antibiotics. Highlights: Enhanced Efficacy: Honey boosts antibiotic effectiveness against UTIs. Resistance Solution: Combines honey to counteract antibiotic resistance. Honey Variability: Different honeys show varied synergistic effects. Keywords: Urinary Tract Infection, Antibiotics, Honey, Synergistic Effect, Antibiotic Resistance